The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0103-97332006000700019
|View full text |Cite
|
Sign up to set email alerts
|

Metric nonsymmetric theory of gravitation: the analogue of the theorem of Birkhoff

Abstract: We prove that a spherically symmetric solution of the field equations of the metric nonsymmetric theory of gravitation developed previously is necessarily static.This is the analogue of the well known Birkhoff theorem in general relativity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The metric is the same one considered in [1], with the components g 00 , g 11 and g [01] depending on r and t, g 00 = γ(r,t) = e ν(r,t) , g 11 = −α(r,t) = −e µ(r,t) ,…”
Section: Spherically Symmetric Vacuum Solution: the Static Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…The metric is the same one considered in [1], with the components g 00 , g 11 and g [01] depending on r and t, g 00 = γ(r,t) = e ν(r,t) , g 11 = −α(r,t) = −e µ(r,t) ,…”
Section: Spherically Symmetric Vacuum Solution: the Static Theoremmentioning
confidence: 99%
“…Recently [1] we have shown that the solution of the field equations of a metric nonsymmetric theory of gravitation [2-I,II] outside a spherically symmetric time-dependent matter distribution is necessarily static. This is the analogue of the theorem of Birkhoff of general relativity (GR).…”
Section: Introductionmentioning
confidence: 99%
“…Next in [3] the conservation laws associated to the theory were studied. In [4] we have proved the analogue of the GR static theorem, that is, that the field outside of a time-dependent spherically symmetric source is necessarily static. More recently [5] a post-Newtonian approximation of the theory was developed with the purpose of application to pulsar binary star systems.…”
Section: Introductionmentioning
confidence: 99%
“…A viable explanation for the questions that have been raised about dark matter is to assume that gravity is not well understood. If we adopt the modied Newtonian dynamics (MOND) theory [16], this theory corrects Newton's laws for small accelerations [7] [8].…”
Section: Introductionmentioning
confidence: 99%